Fifteen-year treatment of metastatic thyroid medullary carcinoma: a case report - Oz Gul, Ozen; Cander, Soner; Sisman, Pinar; Erturk, Erdinc; Ersoy, Canan (The European Research Journal, 2015)
Although very rare, medullary thyroid carcinoma (MTC) is the most aggressive in differentiated thyroid malignancies. We report a 48-year-old male patient with the diagnosis of MTC, who was monitored for fifteen years and showed no serious adverse events due to long-term chemotherapy. Total thyroidectomy, neck dissection, retrosternal nodule excision and pericardiectomy were performed, and radiotherapy was applied to the neck area. Due to progressive metastatic disease cyclophosphamide, dacarbazine, and vincristine were administrated. He tolerated chemotherapy well, and no severe systemic side effects were detected. He died due to multi-organ failure after fifteen years of diagnosis. The only curative treatment is surgery in MTC, however; radiotherapy, chemotherapy, and embolization may be used for patients for whom surgery cannot be performed. Although success rates of systemic chemotherapy are low, it is a treatment option in the progressive metastatic disease.